2003
DOI: 10.1248/cpb.51.1128
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Indole Derivatives with Cardioprotective Activity with Reactive Oxygen Species. Comparison with Melatonin

Abstract: The heart is the most susceptible of all the organs to premature aging and free radical mediated oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…(2008) demonstrated that melatonin can scavenge free DPPH radical. However, Andreadou et al (2003) showed the very weak scavenging activity of melatonin alone on DPPH. The increased reduction of the DPPH radical by plasma may be explained by melatonin's ability to stimulate the physiological enzymatic antioxidant defense and increase of different small antioxidant molecules (Tubaro et al 1998).…”
Section: Discussionmentioning
confidence: 93%
“…(2008) demonstrated that melatonin can scavenge free DPPH radical. However, Andreadou et al (2003) showed the very weak scavenging activity of melatonin alone on DPPH. The increased reduction of the DPPH radical by plasma may be explained by melatonin's ability to stimulate the physiological enzymatic antioxidant defense and increase of different small antioxidant molecules (Tubaro et al 1998).…”
Section: Discussionmentioning
confidence: 93%
“…Among them, indole-3-carbinol has been reported as a free radical scavenger and it has been associated with a variety of benefits including chemoprevention of cancers of the endometrium, lung, mammary tissue, tongue, colon and liver in various animal models [8]. Amine triazolecontaining indole derivatives showed protective activity against the oxidative injury of ischemic myocardium and they scavenged superoxide anion and hydroxyl radical [9]. The combination of indole-3-acetic acid (IAA) and horseradish peroxidase (HRP) has recently been proposed as a novel cancer therapy.…”
Section: Synthesis and Evaluation Of Novel Nzh And N-substituted Indomentioning
confidence: 99%
“…Therefore, the synthesis of MLT analogues with longer half-lives is an interesting topic for researchers 20,21 . Recent research has shown that compounds with an indole ring such as indol-3-propionic acid 22 , indole amine triazole 23 and indolehydrazide/hydrazone derivatives 24,25 have significant antioxidant effects. The indole ring of these compounds is the reactive centre dealing with oxidants due to its high resonance stability and low activation energy barrier towards free radical reactions 24,26 .…”
Section: Introductionmentioning
confidence: 99%